2021
DOI: 10.1371/journal.pone.0254262
|View full text |Cite
|
Sign up to set email alerts
|

Kinesiophobia and its correlations with pain, proprioception, and functional performance among individuals with chronic neck pain

Abstract: Chronic neck pain (CNP) incidence in the general population is high and contributes to a significant health problem. Kinesiophobia (fear of pain to movement or re-injury) combined with emotions and physical variables may play a vital role in assessing and managing individuals with CNP. The study’s objectives are 1) to evaluate the relationship between kinesiophobia, neck pain intensity, proprioception, and functional performance; 2) to determine if kinesiophobia predicts pain intensity, proprioception, and fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
39
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 36 publications
6
39
0
1
Order By: Relevance
“…Further, in the regression analysis, kinesiophobia significantly predicted pain intensity level. These findings in our study are in accordance with studies that showed a significant association between kinesiophobia and pain intensity level in different conditions with musculoskeletal pain [ 20 , 29 , 30 ]. A recent study reveals that fear of movement and catastrophic thoughts lead an individual to painful adverse consequences and affect the neurophysiology of pain regulation [ 31 ].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Further, in the regression analysis, kinesiophobia significantly predicted pain intensity level. These findings in our study are in accordance with studies that showed a significant association between kinesiophobia and pain intensity level in different conditions with musculoskeletal pain [ 20 , 29 , 30 ]. A recent study reveals that fear of movement and catastrophic thoughts lead an individual to painful adverse consequences and affect the neurophysiology of pain regulation [ 31 ].…”
Section: Discussionsupporting
confidence: 94%
“…Limited studies show the association between kinesiophobia and knee proprioception, but studies in other regions with musculoskeletal conditions have shown a positive association. Asiri et al [ 20 ] showed mild to moderate positive correlations between kinesiophobia and cervical joint position errors (extension: r = 0.48, p < 0.001; right rotation: r = 0.31, p = 0.011) [ 20 ]. Similar to our study results, the regression analysis proved that kinesiophobia was a significant predictor of JPS [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Proprioception, according to Sherrington, is the perception of the position, motion of joints, and the perception of force in space 1 . Integrated action of different mechanoreceptors present in muscles, tendons, joint capsules, ligaments contributes to proprioception 2 , 3 . The proprioception is crucial in maintaining balance and body posture with precise and coordinated movements 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%